Directionally supervised cellular automaton for the initial peopling of Sahul. (1st March 2023) - Bradshaw, Corey J.A.; Crabtree, Stefani A.; White, Devin A.; Ulm, Sean; Bird, Michael I.; Williams, Alan N.; Saltré, Frédérik
Abstract: Reconstructing the patterns of Homo sapiens expansion out of Africa and across the globe has been advanced using demographic and travel-cost models. However, modelled routes are ipso facto influenced by migration rates, and vice versa . We combined movement 'superhighways' with a demographic cellular automaton to predict one of the world's earliest peopling events — Sahul between 75000 and 50000 years ago. Novel outcomes from the superhighways-weighted model include ( i ) an approximate doubling of the predicted time to continental saturation (∼10, 000 years) compared to that based on the directionally unsupervised model (∼5000 years), suggesting that rates of migration need to account for topographical constraints in addition to rate of saturation; ( ii ) a previously undetected movement corridor south through the centre of Sahul early in the expansion wave based on the scenarios assuming two dominant entry points into Sahul; and ( iii ) a better fit to the spatially de-biased, Signor-Lipps-corrected layer of initial arrival inferred from dated archaeological material. Our combined model infrastructure provides a data-driven means to examine how people initially moved through, settled, and abandoned different regions of the globe. Highlights: We combined movement 'superhighways' with a demographic model to predict the initial peopling of Sahul. The combined model doubled the predicted time to continental saturation (∼10, 000 years) compared to previous estimates. The model revealed a previously undetected movement corridor south through the centre of Sahul. The combined model provided a better fit to archaeological material than models not weighted by superhighways. The model infrastructure can be applied to the initial movement of people in different regions of the globe.